Financial Benefits from The Millennial Generation in Choosing Islamic Mortgages: Do Digital Marketing Channels Matter? - Amri, Syaiful; Risfandy, Tastaftiyan; Saktiawan, Bimo; Dewi, Toifsa Rosita (Journal of Digital Marketing and Halal Industry, 2025)
The slow provision of houses or residences that are not balanced with the number needed has led to a backlog in Indonesia. As a result, house prices are getting higher, making it difficult for the lower middle class. This problem has become a burden for millennials when building an ideal family with affordable housing. Many think owning a house is a dream that is difficult to realize. To overcome this, the government has tried to provide homeownership credit (kredit pemilikan rumah-KPR) or mortgage loans to provide subsidies for affordable housing in conventional and Sharia or Islamic contracts. Unlike conventional mortgages, Islamic mortgages have a contract as a sale, purchase, or cooperation, not an interest-bearing debt. This study investigates whether financial benefits and digital marketing channels influence the millennial generation's decision to use Islamic mortgages. The research sample consisted of 131 BTN Syariah bank customers born between 1981 and 1996. Our PLS-SEM analysis revealed that financial benefits and digital marketing channels directly affect choosing Islamic mortgages. However, the interaction between the two variables does not have a significant effect. The possibility behind this result is that financial benefits are the main attribute that stands alone regardless of whether it is communicated through digital marketing channels. Therefore, this study suggests that bank managers and stakeholders strive to improve the financial benefits of Islamic mortgages as a core value to attract consumers. In addition, they also need to properly manage the digital marketing channels they have to provide a positive impression.